1978
DOI: 10.1143/jjap.17.1495
|View full text |Cite
|
Sign up to set email alerts
|

Conformational Change of Liquid Crystalline Ethyl-4'-n-Octyloxy Biphenyl Carboxylate at the Liquid Crystal Phase Transitions

Abstract: The temperature dependence of specific heat for the compounds CeNi 4 Cu and YbNi 4 Cu is analysed. These studies are supported by magnetic susceptibility and x-ray photoemission spectroscopy measurements. The scheme of the energy levels created by the splitting due to the crystal electric field is determined from the Schottky contribution to the specific heat. Anomalies observed at low temperatures are discussed in the framework of heavyfermion/Kondo physics. It is found that an external magnetic field has a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

1988
1988
2001
2001

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…These changes can be explained by the change in the molecular conformation. The bands around 200 cm 1 can be assigned to the vibrational modes of the terminal groups 13,14 and the bands around 1500 cm 1 to those of the benzene rings and central CH N group. 15 -18 The bands around 1250 and 1720 cm 1 are assigned to those of the vibrational modes of the carboxyl group.…”
Section: Resultsmentioning
confidence: 99%
“…These changes can be explained by the change in the molecular conformation. The bands around 200 cm 1 can be assigned to the vibrational modes of the terminal groups 13,14 and the bands around 1500 cm 1 to those of the benzene rings and central CH N group. 15 -18 The bands around 1250 and 1720 cm 1 are assigned to those of the vibrational modes of the carboxyl group.…”
Section: Resultsmentioning
confidence: 99%
“…Temperature dependence of the intensity of 415 cm −1 of Raman spectrum (the vibrational mode of the aromatic frame) results in a stepwise increase concord with the phase changes SmE, SmB, SmA and isotropic phase. 12) The E n -N m diagram for the system is given in Fig. 4 mational changes in the core will influence the intensity of the molecular vibrational mode.…”
Section: Effect Of Complex Molecular Structure On the Stringmentioning
confidence: 99%
“…Raman spectroscopies have shown that the terminal chains of liquid crystal molecules melt as liquid crystal compounds undergo the first liquid crystal phase transition. [4][5][6][7] Raman studies have also shown that the aromatic frame of liquid crystal molecules changes its conformation at liquid crystal phase transitions. [7] Liquid crystal compounds are mostly composed of two parts, rigid central mesogen and one or two terminal groups.…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6][7] Raman studies have also shown that the aromatic frame of liquid crystal molecules changes its conformation at liquid crystal phase transitions. [7] Liquid crystal compounds are mostly composed of two parts, rigid central mesogen and one or two terminal groups. In addition, almost all of the rod-like liquid crystals reported so far had para-substituted terminal groups.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation